Forgivness, kebermaknaan hidup dan kebahagiaan remaja yang tinggal dipanti asuhan - Lapiana; Adnani Budi Utami; Karolin Rista (INNER: Journal of Psychological Research, 2022)
Abstract The purpose of this study was to determine whether there is a relationship between forgiveness and the meaning of life with the happiness of adolescents who live in orphanages. The type of research used in this research is quantitative research. The subjects in this research are 60 teenagers who live in Pondok Kasih orphanage in Surabaya, aged 13-21 years. The data analysis technique used to see the relationship between forgiveness and the meaning of life with adolescent happiness is the Spearmant's Brown correlation test using SPSS 23.0 for windows. The results show that there is a positive relationship between Forgiveness and happiness, which means that the higher the level of happiness in adolescents, the higher the level of happiness, and vice versa, the lower the level of forgiveness of adolescents, the lower the level of happiness. And there is a positive relationship between the meaning of life and happiness. This means that the higher the level of happiness, the higher the level of happiness, and vice versa, the lower the level of happiness. So that it can be said that there is a positive relationship between forgiveness and the meaning of life with the happiness of teenagers living in orphanages. Keywords: Forgiveness, Meaning of Life, Happiness